2008
DOI: 10.1016/j.neuron.2008.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Hippocampal and Extra-Hippocampal NR2B-Containing NMDA Receptors to Performance on Spatial Learning Tasks

Abstract: Controversy revolves around the differential contribution of NR2A- and NR2B-containing NMDA receptors, which coexist in principal forebrain neurons, to synaptic plasticity and learning in the adult brain. Here, we report genetically modified mice in which the NR2B subunit is selectively ablated in principal neurons of the entire postnatal forebrain or only the hippocampus. NR2B ablation resulted in smaller NMDA receptor-mediated EPSCs with accelerated decay kinetics, as recorded in CA1 pyramidal cells. CA3-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
194
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 227 publications
(211 citation statements)
references
References 60 publications
13
194
3
1
Order By: Relevance
“…Whereas ablation of the GluN2B subunit in both hippocampus and cortex impaired watermaze learning 49 (but importantly had no effect on the visible platform control task), deletion restricted to just the hippocampus had no effect 67 . Thus, these data clearly demonstrate that NMDARs either elsewhere in the extended hippocampal formation, such as the entorhinal cortext 73 or subiculum 5 , or across the wider cortical mantle, are necessary for spatial memory performance.…”
Section: Extra-hippocampal Nmdars and Long-term Spatial Memorymentioning
confidence: 93%
See 1 more Smart Citation
“…Whereas ablation of the GluN2B subunit in both hippocampus and cortex impaired watermaze learning 49 (but importantly had no effect on the visible platform control task), deletion restricted to just the hippocampus had no effect 67 . Thus, these data clearly demonstrate that NMDARs either elsewhere in the extended hippocampal formation, such as the entorhinal cortext 73 or subiculum 5 , or across the wider cortical mantle, are necessary for spatial memory performance.…”
Section: Extra-hippocampal Nmdars and Long-term Spatial Memorymentioning
confidence: 93%
“…Notably, the deficit in Grin1 ΔDGCA1 mice during spatial reversal testing reflects their increased perseveration to the old platform location. This is evident by the greater time spent in the training quadrant during the transfer test (which was performed in extinction), conducted at the end of the initial watermaze acquisition training ( Figure 2b, Transfer Test; see also 67 ).…”
Section: Grin1mentioning
confidence: 99%
“…While human post-mortem data supports that NMDARs and their subunits are altered in schizophrenia, whether they be increased or decreased in brain regional 1908, displayed increased locomotor activity (10-30mg/kg) and impaired response inhibition (1-10mg/kg) but no disruption to PPI (1-10mg/kg) (Higgins et al, 2003). A recent study has shown that there are deficits in both spatial and non-spatial memory following a forebrain-specific deletion of NR2B, whereas hippocampal-restricted deletion of NR2B induces a selective working memory deficit (von Engelhardt et al, 2008). Mice with a complete knockout of NR2B die shortly after birth and therefore cannot undergo behavioural analysis.…”
Section: Nmda Receptor Subunits and Schizophreniamentioning
confidence: 99%
“…pAAV-double floxed mCherry was a kind gift from K. Deisseroth and AAV was produced as previously described (Monory et al, 2006). Conditional knock-out (KO) mice for Grin2B (GluN2B fl/fl ) (von Engelhardt et al, 2008) and Grin1 (GluN1 fl/fl ) (Niewoehner et al, 2007), heterozygous lacZ reporter (B6-gt(ROSA) 26SOR lacZ) mice (Soriano, 1999), and Grin2A (GluN2A Ϫ/Ϫ ) KO mice (Sakimura et al, 1995) were bred in a C57BL/6N background (Charles River). Mice of either sex were used.…”
Section: Methodsmentioning
confidence: 99%